2022
DOI: 10.1007/s40292-022-00524-7
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine for the Clinical Management of Diabetes; Implications and Considerations After COVID-19 Experience

Abstract: Telemedicine is a clinical approach that was seldom used in the day-to-day practice, if not only in certain settings, before the COVID-19 pandemic. As stated by the WHO, telemedicine is: the delivery of health care services, where distance is a critical factor, by all health care professionals using information and communication technologies (ICT) for the exchange of valid information for diagnosis, treatment and prevention of disease and injuries, …. Telemedicine has actually represented the most useful and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 77 publications
(69 reference statements)
1
31
0
Order By: Relevance
“…As a consequence, the access to health care providers became difficult and limited. Although the widespread increase of telemedicine slowly counterbalanced this drawback in diabetes management [ 18 ], the impact of COVID-19 pandemic on treatment patterns should be considered as an important factor affecting therapeutic practice in patients withT2DM.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, the access to health care providers became difficult and limited. Although the widespread increase of telemedicine slowly counterbalanced this drawback in diabetes management [ 18 ], the impact of COVID-19 pandemic on treatment patterns should be considered as an important factor affecting therapeutic practice in patients withT2DM.…”
Section: Discussionmentioning
confidence: 99%
“…The management of DM usually requires periodic face-to-face interactions with the healthcare providers, but during the COVID-19 pandemic alternative technology-based methods and strategies have been implemented, in order to support patients and provide continued healthcare services [16]. Telehealth turned out to be crucial for delivery of these services to DM patients and was widely used throughout the pandemic [17]. It was provided through videoconferences or telephone calls, if the necessary technologies were not available.…”
Section: Introductionmentioning
confidence: 99%
“…Telemedicine has proven to be useful and effective for providing care to people with diabetes during the COVID-19 pandemic. 1 , 2 However, the impact varies by each nation and type of diabetes. 3 , 4 A previous systematic review and meta-analysis of randomized controlled trials reported that telemedicine was superior to usual care in improving HbA1c levels in adults with T2D.…”
Section: Introductionmentioning
confidence: 99%